Analysis of the spatial distribution of Police Stations on services to vulnerable urban areas (Case Study: Urmia City) - Ahmad Aftab; Ali Akbar Taghilo; Akbar Houshmand (تحقیقات کاربردی علوم جغرافیایی)
The continuous and active presence of disciplinary centers has an important role in ensuring security and peace in cities.Therefore the fair and efficient distribution of law enforcement centers in urban areas is an important factor in meeting this basic need.Therefore, the present study aims to investigate the service of police stations on vulnerable areas of Urmia.The descriptive-analytical research method used in this study is applied.The results of the study show that the vulnerability zoning of the city of Urmia is in four categories from very high to very low. About 68 km2 of the whole area of the city is known to be highly vulnerable.Most of the northern (informal settlements of Region 2) and central (old districts of four region) settlements of Urmia are the most vulnerable areas due to the high density of population and housing,with most of the politically sensitive, commercial and administrative offices in these areas.The results of the network analysis based on standard time (12 minutes) indicate that the 28.9% (24 km2) of the Urmia Vulnerable Areas was not covered by the police stations.Within 12 minutes the police stations of Urmia city have quick access to 55 km2 of about 75 km2 area with high vulnerability and about 20 km2 of this area also without timely access. In terms of the police stations access to low vulnerability areas,the results also show that from about 15 km2 of these areas to 3 km2 have quick access, indicates that there is no quick access to these 12 km2